2021
DOI: 10.1097/md.0000000000026601
|View full text |Cite
|
Sign up to set email alerts
|

The enhanced bioavailability of free curcumin and bioactive-metabolite tetrahydrocurcumin from a dispersible, oleoresin-based turmeric formulation

Abstract: Background: Curcuminoids have been widely studied for human health and disease applications, yet bioavailability remains a hurdle to actualizing all the benefits ascribed to them. The lack of standardization in analysis method, confusion about what constitutes an ideal analyte, and conflicting thoughts around dosing strategies have made it difficult to draw parity between bioavailability and bioactivity and establish a baseline for formulation comparisons. Methods: This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
0
6
0
2
Order By: Relevance
“…A study in healthy volunteers compared the pharmacokinetics of Curcugen (a novel dispersible 50% curcuminoid extract) with standard extract (i.e., 95% curcuminoids). Curcugen was 16.9-, 39-, 49.5-, 43.5-, 46.8-, and 52.5-fold higher than C-95 in terms of AUC0-t, Cmax, total curcumin, total DMC, total BDMC and total curcuminoids, respectively, as well as 31-fold higher relative bioavailability [66]. In another study comparing the pharmacokinetics of nano-curcumin with free curcumin (500 mg/kg dose) in rats, it was found that the concentration of free curcumin in the plasma, liver, kidney, and colon was higher than nano-curcumin.…”
Section: Pharmacokinetics Of Different Curcumin Dosage Preparationsmentioning
confidence: 86%
“…A study in healthy volunteers compared the pharmacokinetics of Curcugen (a novel dispersible 50% curcuminoid extract) with standard extract (i.e., 95% curcuminoids). Curcugen was 16.9-, 39-, 49.5-, 43.5-, 46.8-, and 52.5-fold higher than C-95 in terms of AUC0-t, Cmax, total curcumin, total DMC, total BDMC and total curcuminoids, respectively, as well as 31-fold higher relative bioavailability [66]. In another study comparing the pharmacokinetics of nano-curcumin with free curcumin (500 mg/kg dose) in rats, it was found that the concentration of free curcumin in the plasma, liver, kidney, and colon was higher than nano-curcumin.…”
Section: Pharmacokinetics Of Different Curcumin Dosage Preparationsmentioning
confidence: 86%
“…3-5%), and THC being the major metabolite of curcumin [7]. We measured the plasma levels of CUR, DMC, BDMC, and THC which are known to be responsible for the diverse bioactivity of curcuminoids [8,[24][25][26][27] and represented the data for total curcuminoids. Our study results showed that the plasma concentrations of total curcuminoids and its bioavailability were significantly higher for both doses (250 and 500 mg) of CU?…”
Section: Discussionmentioning
confidence: 99%
“…Major components of curcuminoids include curcumin (CUR), demethoxycurcumin (DMC), and bisdemethoxycurcumin (BDMC), with CUR being up to 77% of the total curcuminoid content [4][5][6]. Tetrahydrocurcumin (THC) is a primary metabolite of curcumin that has better aqueous solubility, chemical stability, bioavailability, and antioxidative activity [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The novel CURCUGEN, a dispersible formulation with 50% curcuminoids—concentrated turmeric extract—demonstrated that the relative bioavailability of total tetrahydrocurcumin was 31 times higher compared to the standard curcumin reference product, curcuminoid 95% standardized extract (C-95). In addition, CURGUGEN had C max and the area under de curve (AUC0-t) was 16.1 times higher and 39 times higher than that of C-95 [ 29 ]. Furthermore, Curcuwin Ultra+ (CU+), a novel formulation designed to protect curcuminoids from intestinal degradation, demonstrated a significant higher total systemic exposure and C max for total curcuminoids compared with 95% turmeric extract (TUR 1800).…”
Section: Curcuminmentioning
confidence: 99%